Pemetaan Laju Erosi Menggunakan Metode RUSLE dan Google Earth Engine Pada DAS Serayu - Imawan, Renvil; Pinem, Agusta Praba Ristadi (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
The Serayu Watershed, which includes Wonosobo, Banjarnegara, Purbalingga, Banyumas, to Cilacap in Central Java, faces erosion challenges due to the rugged topography. This research presents a new approach in mapping erosion rates in the Serayu watershed by combining the Revised Universal Soil Loss Equation (RUSLE) method and Google Earth Engine (GEE) technology. Utilizing satellite imagery from GEE, including annual rainfall data, soil texture, slope, vegetation index, and land conservation from the period 2021-2022, this study revealed an interesting finding: the Serayu watershed experienced heavy erosion, exceeding 40 tons/ha/year, especially in Purbalingga, Banjarnegara, and Wonosobo. The main innovation of this research lies in its approach which provides a new perspective in erosion analysis in the Serayu watershed. The results provide deep insights for natural resource management, environmental protection, sustainable land use planning, and environmental change monitoring. The integration of GEE not only accelerates analysis, but also brings an innovative dimension that differentiates this research from previous research in similar areas.